SURG-06. MANAGEMENT OF HYDROCEPHALUS IN ADULT PATIENTS WITH BRAIN METASTASES. (9th November 2020) - Vaynerman, A; Coombs, L; Nickols, H; LaRocca, R; Sinicrope, K; Ishihara, D; Spalding, A; Sun, D
Abstract: BACKGROUND: Traditionally patients presenting with hydrocephalus in the setting of brain metastases were associated with poor outcomes. However, in the area of improved systemic therapies, the prognosis of brain metastases has improved, warranting investigation into the management of concomitant hydrocephalus. METHODS: We conducted a retrospective review of 12 consecutive patients with brain metastases presenting with hydrocephalus treated with either endoscopic third ventriculostomy (ETV) or ventriculoperitoneal shunt (VPS) from June 2013 to December 2018. We then compared our outcomes to 77 historical controls from the literature to test the hypothesis that management of hydrocephalus in patients who respond to systemic therapy is associated with improved outcomes. RESULTS: The medial overall survival in our cohort was 182 days compared with 91 days in the reported previous studies, with an odds ratio of 0.5 (95% CI 0.24-1.04). In the 5 patients who underwent ETV, the median survival was 182 days versus 77 days reported in the literature, an odds ratio of 0.42 (95% CI 1.28-1.40). Patients with one brain metastasis did not reach median survival with 4 of 5 patients alive at last follow up, while only 3 of 7 patients with at least two metastases were alive at follow up with a median survival of 182 days. Patients who had immunotherapy were associated with improved survival, while leptomeningeal carcinomatosis still was associated with a negative outcome. CONCLUSIONS: Patients with brain metastases and hydrocephalus who underwent neurosurgical CSF diversion had improved survival compared with historical controls, particularly in patients with one metastasis or who received immunotherapy. This study supports initial interdisciplinary evaluation of patients with brain metastases by medical and radiation oncology together with neurosurgery to facilitate immediate systemic therapy after relief of hydrocephalus.